EFEKTIVITAS PROBLEM SOLVING DAN PROBLEM POSING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMPN 47 BATAM - Era Rianti; Fitrah Amelia (Universitas Riau Kepulauan, 2018)
This research aims to: (1). Knowing the effectiveness of the learning model problem solving toward of student’s mathematics communication abilities, (2). Knowing the effectiveness of the learning model problem posing toward of student’s mathematics communication abilities, (3). Knowing the difference between the effectivenees of the learning model problem solving and problem posing toward of student’s mathematics communication abilities. The experiment was using quasi-experiment methode. Population in this research were students of class 7th SMPN 47 Batam, a sampling technique that uses purposive sampling. Instrument in this research a essay test. The results show that: (1). The learning model problem solving not effectively toward of student’s mathematics communication abilities, (2). The learning model problem posing effectively toward of student’s mathematics communication abilities, (3). There is no difference in effectiveness between the learning model of problem solving and problem posing toward of student’s mathematics communication abilities.Keywords: problem solving learning model, problem posing learning model, and mathematics communication abilities